Spatial and temporal distribution of Rocky Mountain Spotted Fever in Mexico: Study period 2015-2023 - Pérez-Montiel, Cielo E. (2025)
Rocky Mountain spotted fever (RMSF) is an acute infection characterized by febrile symptoms, caused by the bacteria Rickettsia rickettsii. The aim of this research was to determine the spatial and temporal distribution of RMSF in Mexico during the period 2015-2023. Information from the epidemiological bulletins of the National Epidemiological Surveillance System of Mexico (2015-2023) of the Ministry of Health of Mexico was analyzed. Prevalence rates of RMSF were calculated by state of the Mexican Republic, the temporal behavior of RMSF was determined through an endemic channel at the country level and by geographic area, and the spatial behavior was determined through the spatial statistic SCAN. The states with the highest prevalence rate of RMSF were Baja California and Sonora with more than 70 cases per 1,000,000 inhabitants. RMSF in the Mexican Republic occurs throughout the year, with endemic peaks in the months of June, July, and August. Three FMMR clusters were identified in the Mexican Republic, the primary cluster was in Baja California with a relative risk of 74.95.